2013
DOI: 10.1185/03007995.2013.779575
|View full text |Cite
|
Sign up to set email alerts
|

Association of baseline C-reactive protein and prior anti-tumor necrosis factor therapy with need for weekly dosing during maintenance therapy with adalimumab in patients with moderate to severe Crohn’s disease

Abstract: These subgroup analyses suggest that in patients with moderately to severely active CD, weekly dosing may be most effective in the anti-TNF-experienced patients with elevated CRP at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
7
1
2
Order By: Relevance
“…This finding is consistent with a previously published report from CHARM that showed that patients who dose escalated were able to regain efficacy . A recently published analysis from CHARM suggested that weekly dosing may be associated with greater efficacy than every other week dosing in patients with elevated CRP who have lost response to treatment with a prior anti‐TNF agent …”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with a previously published report from CHARM that showed that patients who dose escalated were able to regain efficacy . A recently published analysis from CHARM suggested that weekly dosing may be associated with greater efficacy than every other week dosing in patients with elevated CRP who have lost response to treatment with a prior anti‐TNF agent …”
Section: Discussionsupporting
confidence: 91%
“…Although it is tempting to compare clinical trials of drugs with similar pharmacotherapy targets, baseline subject demographics must be controlled for in a comparative analysis. A correlation between baseline CRP levels and response to TNF blockers has been previously observed in ankylosing spondylitis (11) and Crohn's disease (12). Interestingly, one large observational study showed that increased CRP levels at baseline are sometimes associated with good treatment response and drug survival, that is, the length of time a drug is used before termination (6).…”
Section: Discussionmentioning
confidence: 73%
“…The current retrospective cohort study confirms that CRP is an important factor in the individualised therapy of CD. While an elevated CRP has been shown to be a good predictor of response to adalimumab initiation, early CRP normalisation is associated with sustained clinical response . In a Belgian retrospective multi‐centre adalimumab cohort study, an elevated CRP was associated with a lower response to dose escalation to adalimumab every week, but was not predictive of subsequent dose de‐escalation .…”
Section: Discussionmentioning
confidence: 97%